Analysis of Audiences' Interpretation of Ganjar Pranowo's Image in MNC Group's Adzan Show (Reception Study on Young People) - Bashirotul Insiya (Gema Wiralodra, 2024)
Ganjar Pranowo is one of the political figures with a fairly high electability rate. However, when he appeared as a model in the MNC Group television station's call to prayer broadcast, it became a polemic in society, thus reducing his electability. Young people in the general election became the largest voter for the upcoming 2024 election, compared to older people. The purpose of this study was to see the meaning of young people towards the image of Ganjar Pranowo in the MNC Group call to prayer broadcast. The textual analysis method uses the concept of the codes of television, while the meaning analysis method uses the Stuart Hall encoding decoding concept. The dominant meaning of this call to prayer broadcast depicts the figure of Ganjar Pranowo who is religious and there is no campaign element in it. This study reveals the diversity of meanings of young audiences. Ganjar Pranowo's image was well received before this call to prayer broadcast. Some of them began to decline seeing Ganjar Pranowo's image after the call to prayer broadcast. Where there are two informants in the dominant hegemonic position and two others in the opposition position. Apart from gender perspective, diversity of meanings also occurs due to understanding of political values and insights.